2021
DOI: 10.3389/fonc.2021.691246
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Monitoring of Treatment Response to Brain Tumor Immunotherapy

Abstract: Immunotherapy has revolutionized care for many solid tissue malignancies, and is being investigated for efficacy in the treatment of malignant brain tumors. Identifying a non-invasive monitoring technique such as metabolomics monitoring to predict patient response to immunotherapy has the potential to simplify treatment decision-making and to ensure therapy is tailored based on early patient response. Metabolomic analysis of peripheral immune response is feasible due to large metabolic shifts that immune cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 100 publications
(139 reference statements)
0
10
0
2
Order By: Relevance
“…Meanwhile, TAMs initiate proinflammatory (M1) or immunosuppressive (M2) function depending on their polarization status. 34 , 35 M2-like macrophage was the main macrophage type that induced immunosuppressive microenvironment and thus accelerated glioma progression. Our results indicated that ARPC1B in macrophages played a tumor-promoting role in glioma malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, TAMs initiate proinflammatory (M1) or immunosuppressive (M2) function depending on their polarization status. 34 , 35 M2-like macrophage was the main macrophage type that induced immunosuppressive microenvironment and thus accelerated glioma progression. Our results indicated that ARPC1B in macrophages played a tumor-promoting role in glioma malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to their special metabolic mode, cancer cells tend to utilize glucose and produce excessive lactate even in an environment with a sufficient oxygen supply and release a large amount of lactate into the extracellular microenvironment, thereby causing acidosis, angiogenesis, and immunosuppression simultaneously (58). Consequently, this kind of metabolism modulation breaks the balance of the immune state in the tumor, resulting in an enhanced immunosuppressive effect by promoting the CD4+ CD25+ regulatory T (Treg) cell metabolic profiles and maintaining the acidity of the TME (60). However, excessive lactate attenuates the proliferation of immunocytes, including CD8+ T, natural killer (NK), and dendritic cells (61)(62)(63).…”
Section: Discussionmentioning
confidence: 99%
“…These changes help cells sustain the high proliferation rate and adapt to continuous fluctuations in the tumor microenvironment, particularly changes in nutrients and oxygen availability (95)(96)(97). Besides, numerous studies suggested a key role of these metabolic adaptations in immune cell dysfunction and cancer immune escape via acidification of the TME, secretion of immunosuppressive cytokines, and induction of epigenetic modifications in immune cells (156)(157)(158). Alongside this, similar metabolic reprogramming occurs on the surrounding immune cells, affecting their activation and function, altering the anti-cancer immunity, and thereby enabling tumor cells to evade the immunosurveillance system (159).…”
Section: Discussionmentioning
confidence: 99%